Lipase-catalyzed incorporation of n−3 PUFA into palm oil - Fajardo, A. Ramírez; Akoh, Casimir C.; Lai, O. M. (Wiley, 2003)
Two immobilized upases, IM60from Rhizomucor miehei and QLM from Alcaligenes sp., were used as biocatalysts for the modification of the FA composition of palm oil by incorporating n-3 PUFA. Acidolysis and interesterification reactions were conducted with hexane as organic solvent, and the products were analyzed by using CLC, After a 24-h incubation in hexane, there was an average incorporation of 20.8% EPA and 15.6% DHA into palm oil, respectively, while the percentages of palmitic and oleic acids in palm oil decreased by 28.8 and 11.8%, respectively. Higher EPA and DHA incorporation was obtained when EPAX (fish oil concentrate high in n-3 PUFA) was used in the ethyl ester form (interesterification reaction) than in the free acid form (acidolysis) in the presence of Lipozyme IM60 lipase. Lipase QLM was found to discriminate against EPA, and it showed slightly better catalytic activity for DHA in the free acid form than in the ethyl ester form. Generally, as the mole ratio of the acyl donor to TAG increased, the percentage incorporation of EPA and DHA increased; however, reactions catalyzed by Lipozyme IM60 did not show increases in the incorporation beyond a TAG/EPAX mole ratio of 3. When limitations due to mass transfer were not a factor, an increase in the reactant amount also gave an increase in the percentage incorporation of the n-3 PUFA. Palm oil containing EPA and DHA was successfully produced and may be beneficial in certain food and nutritional applications.